Proceedings of the 2013 Conference on Computer Supported Cooperative Work 2013
DOI: 10.1145/2441776.2441845
|View full text |Cite
|
Sign up to set email alerts
|

Putting ubiquitous crowd-sourcing into context

Abstract: Abstract:Ubiquitous crowd-sourcing has become a popular mechanism to harvest knowledge from the masses. OpenStreetMap (OSM) is a successful example of ubiquitous crowd-sourcing, where citizens volunteer geographic information in order to build and maintain an accurate map of the changing world. Research has shown that OSM information is accurate, by comparing it with centrally maintained spatial information such as Ordnance Survey. However, we find that coverage is low and non uniformly distributed, thus chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…Quality control mechanism similar to those employed in crowdsourcing (i.e., majority consensus is used to maintain Wikimapia data [70]) as well as use of heuristics (e.g., POI data entry of a café in the middle of a historic park tend to be erroneous [70]) should not be present is also used to assure its data accuracy However, its coverage still falls behind that of other official dataset, especially in rural areas and in countries where OpenStreetMap is less popular [133]. This geographic data coverage bias is common in VGI [74,124,145]. In chapter 6, we investigate the quality and quantity of data collected via our remote data collection methods to see if our volunteer-based methods are viable for collecting geographical information about street-level accessibility.…”
Section: Volunteered Geographic Informationmentioning
confidence: 99%
“…Quality control mechanism similar to those employed in crowdsourcing (i.e., majority consensus is used to maintain Wikimapia data [70]) as well as use of heuristics (e.g., POI data entry of a café in the middle of a historic park tend to be erroneous [70]) should not be present is also used to assure its data accuracy However, its coverage still falls behind that of other official dataset, especially in rural areas and in countries where OpenStreetMap is less popular [133]. This geographic data coverage bias is common in VGI [74,124,145]. In chapter 6, we investigate the quality and quantity of data collected via our remote data collection methods to see if our volunteer-based methods are viable for collecting geographical information about street-level accessibility.…”
Section: Volunteered Geographic Informationmentioning
confidence: 99%
“…Zielstra et al [45] found that road coverage in Germany sharply decreases as we move away from city centres and Girres et al [13] discovered a positive correlation between the number of OSM road 'objects' in an area and number of OSM contributors in that area. Shifting focus from the road network to points-of-interest (POIs), Mashhadi et al [30] found that both socio-economic factors (e.g., income deprivation) and physical distance from the city centre are negatively correlated with coverage in London, UK. Another well known example of urban 7 http://www.navteq.com/ crowd-sourcing application is Cyclopath, 8 a geo-wiki that is being successfully used to digitally map route information for cyclists in Minneapolis.…”
Section: Related Workmentioning
confidence: 99%
“…In terms of spatial unit of analysis, previous studies have shown that factors such as population density and deprivation are correlated with coverage of crowd-sourced urban information [30]. We have thus chosen to operate at a level of granularity in London for which such information is available.…”
Section: Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the great popularity that geo-wiki systems received in the last years, they have seen far less research attention, with the exception of recent studies on accuracy and coverage of OpenStreetMap 1 (OSM) where the accuracy is shown to be high [7,14] and coverage to be non-uniformly distributed [28,13]. However, users behaviour in this domain is by far less investigated subject and thus requires more research effort to be well understood.…”
Section: Introductionmentioning
confidence: 99%